Bioactivity of POPs and their effects in mosquitofish in Sydney Olympic Park, Australia - Rawson, Christopher; Tremblay, L.; Warne, M.; Ying, G.; Kookana, R.; Laginestra, E.; Chapman, J.; Lim, R. (Elsevier, 2009)
The site of the 2000 Olympic Games (Sydney Olympic Park (SOP), Sydney, Australia) was contaminated by persistent organic pollutants (POPs) prior to remediation in the 1990s. This study investigates the bioactivity of POPs in the sediment and water of wetlands across SOP by in vitro 2,3,7,8-TCDD equivalence (TCDDeq) measurement (H4IIE cell line bioassay). Further, it examines whether disturbance of these sediments is likely to mobilise ligands for this receptor into the water column. Exposure to aryl hydrocarbon receptor (AhR) ligandswas measured in vivo using hepatic cytochrome P4501A (CYP1A) induction (EROD) in the mosquitofish (Gambusia holbrooki). Aqueous TCDDeq ranged from 0.013 to 0.057 pM in SOP wetlands which was significantly (pb0.05) less that in urban reference sites. These concentrations were not correlated to physical or chemical characteristics of the wetlands. In the sediments, TCDDeq ranged from 0.0016 to 7.06 µg/kg and these were not significantly (p=0.05) different to that measured in urban reference sites. Simulated disturbance of small quantities of sediment inwater samples significantly (pb0.05) increased the levels of TCDDeq measured in the water. Sediment TCDDeq was correlated to sediment SPAH concentration in 2006 and sediment SPCB, SDDT concentrations and fine sediment grain size in 2005. While fish at one SOP wetland had hepatic EROD activity elevated above the estimated basal level for this species, these were at the lower end of the range measured in urban impacted, non-remediated wetlands. EROD activitywas positively correlated with both the sediment SPCB load and aqueous TCDDeq. Increased catchment size was correlated with increased EROD activity suggesting an even spread of POPs throughout the residential areas of the Sydney metropolitan area. The concentration of bioactive POPs in the wetlands of SOP is therefore low relative to urban reference sites demonstrating the ongoing success of the remediation program.